2018
DOI: 10.1371/journal.pbio.2003864
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum-plasma membrane contact sites integrate sterol and phospholipid regulation

Abstract: Tether proteins attach the endoplasmic reticulum (ER) to other cellular membranes, thereby creating contact sites that are proposed to form platforms for regulating lipid homeostasis and facilitating non-vesicular lipid exchange. Sterols are synthesized in the ER and transported by non-vesicular mechanisms to the plasma membrane (PM), where they represent almost half of all PM lipids and contribute critically to the barrier function of the PM. To determine whether contact sites are important for both sterol ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
206
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(221 citation statements)
references
References 102 publications
11
206
0
Order By: Relevance
“…We first evaluated the effect of ist2 mutations on general lipid homeostasis in the cell. Lipidomic analysis of whole cell extracts showed that both osh6D osh7D and ist2D cells had a dramatic (2.5-fold) decrease in PS levels compared to WT, similar to the decrease in PS observed in a strain lacking all ER-PM tethers (Quon et al, 2018). In contrast, the levels of phosphatidylcholine (PC), phosphatidylethanolamine (PE) or phosphatidylinositol (PI) were not significantly affected ( Fig.…”
Section: Ist2 Is Required For Osh6-mediated Ps Transport To the Pmsupporting
confidence: 57%
“…We first evaluated the effect of ist2 mutations on general lipid homeostasis in the cell. Lipidomic analysis of whole cell extracts showed that both osh6D osh7D and ist2D cells had a dramatic (2.5-fold) decrease in PS levels compared to WT, similar to the decrease in PS observed in a strain lacking all ER-PM tethers (Quon et al, 2018). In contrast, the levels of phosphatidylcholine (PC), phosphatidylethanolamine (PE) or phosphatidylinositol (PI) were not significantly affected ( Fig.…”
Section: Ist2 Is Required For Osh6-mediated Ps Transport To the Pmsupporting
confidence: 57%
“…While we have focused here on the role of Ltc1 in retrograde sterol flow from the PM, our observations suggest that Osh41 may promote PM sterol levels during steady-state growth and Osh42 may control sterol flow away from vacuoles. Osh41 and Osh42 are related to S. cerevisiae Osh4, which binds sterols in vitro (de Saint-Jean et al, 2011;Im et al, 2005;Schulz et al, 2009) and is proposed to promote ER to PM sterol transport by using the counter-gradient of PI4P (Moser von Filseck et al, 2015), although in vivo data suggest a role in membrane sterol organization rather than sterol transport (Georgiev et al, 2011;Quon et al, 2018;Raychaudhuri et al, 2006). These observations demonstrate that D4H is a highly valuable tool to study the intracellular trafficking of sterols.…”
Section: The D4h Biosensor Gives Novel Insights Into Sterol Distributmentioning
confidence: 92%
“…Intriguingly, while most LTPs localize to dedicated organelle contact sites, S. cerevisiae mutants lacking all six known ER-PM tethering proteins show normal anterograde, and only partially diminished retrograde sterol transport (Quon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic phenotypes of stt4 G1782D and sac1 mutants suggested derangements in how PtdSer synthesis is regulated or otherwise organized. The role of ER-plasma membrane (PM) contact sites as regulatory/organizing nodes for lipid synthesis has been noted (Quon, Sere et al, 2018).…”
Section: Ptdins4p Homeostasis Indirectly Modulates Psd2-dependent Ptdmentioning
confidence: 99%
“…To determine whether simple tethering of ER to the PM was sufficient to rescue PtdSer homeostasis in tether cells, an artificial ER-PM protein tether was expressed in the double mutant (Quon, Sere et al, 2018). Expression of this artificial staple failed to rescue [ 3 H]-PtdSer levels in tetherΔ yeast and failed to restore growth of tetherΔpsd1Δ cells in Etn-free liquid media ( Figure 7D).…”
Section: Ptdins4p Homeostasis Indirectly Modulates Psd2-dependent Ptdmentioning
confidence: 99%